The role of LISS (less invasive stabilisation system) in the treatment of peri-knee fractures - Liu, Fan; Tao, Ran; Cao, Yi; Wang, Youhua; Zhou, Zhenyu; Wang, Hong; Gu, Yongqiang (Injury, 2009)
The purpose of present study was to evaluate the role of LISS after a large series of patients in whom a fracture around the knee had been treated with this uniform technique. Between April 2004 and September 2006, 210 patients with a total of 216 fractures around the knee were treated with LISS, all at the Affiliated Hospital to Nantong University. Patients were followed for a mean of 27 months (range 12–42 months). 26 patients were excluded from the study. The remaining 184 patients with a total of 189 fractures of either distal femur (85 cases) or proximal tibia (104 cases) were available for analysis. The mean age of these patients was 49 years (range 18–82 years). Immediate postoperative X-rays showed the alignment of bone and joint was satisfactorily maintained with LISS in all cases and an ideal implant position in 176 cases (93%). All cases healed the fracture without non-union. The mean time to union was 15 weeks (range 12–27 weeks) for the femoral and 16 weeks (range 12–27 weeks) for the tibia fractures. Functional assessment was performed using HSS (hospital for special surgery) score. At the time of the latest follow-up, 158 patients (86%) had an excellent or good outcome. Overall, 3 patients were subject to a salvage operative procedure due to implant failure. Three cases underwent secondary bone graft for open fractures. Superficial and deep infection was found each in one patient and both were treated successfully. Hardware prominence irritation was found in 2 patients. LISS was removed in 27 patients after bone healing, and this procedure was neither less invasive nor easy as imagined. The results indicate the LISS system is perfect but by no means unique in the treatment of the fractures around the knee. The fixation is adequate enough to maintain alignment and obtain union with a low incidence of complications even in patients with osteoporotic bone. We firmly believe favourable results can be achieved when this device is combined with correct indications as well as skillful techniques.